Isolation of two δ5 polymethylene interrupted fatty acids from Podocarpus falcatus by countercurrent chromatography - Hammann, Simon; Schröder, Markus; Schmidt, Carolin; Vetter, Walter (Journal of Chromatography A, 2015)
The lipids of gymnosperms frequently feature unusual polyunsaturated fatty acids (PUFAs) such as sciadonic acid (20:3Δ5,11,14) and juniperonic acid (20:4Δ5,11,14,17) showing a first double bond on C-5 which is separated from the next double bond by five methylene units. Compared to “classic” fatty acids, these fatty acids are not easily commercially available and their prices are quite high. For this reason, we wished to isolate those fatty acids from the seed oil of Podocarpus falcatus by countercurrent chromatography (CCC) after conversion of the fatty acids to methyl esters (FAMEs). The contribution of sciadonic acid (20:3Δ5,11,14) and juniperonic acid (20:4Δ5,11,14,17) in the unfractionated sample was 10% and 6% respectively, while oleic acid (18:1Δ9) and linoleic acid (18:2Δ9,12) were the major fatty acids. After a first CCC run with FAMEs from Podocarpus falcatus, fractions enriched in the target compounds were chosen for subsequent isolation by means of two subsequent CCC runs. Initially, 13 mg of juniperonic acid was recovered with a purity of 92% according to analysis by gas chromatography with mass spectrometry (GC/MS). Further purification of this fraction yielded 2.7 mg with a purity of 99% according to GC/MS. The isolation of sciadonic acid was hampered by high amounts of linoleic acid with the same equivalent chain length in suitable fractions of the first CCC separation. After an enrichment step by CCC, the critical pair sciadonic acid and linoleic acid was finally separated as free fatty acids. After this step, 4.4 mg of sciadonic acid was recovered with 99% purity. The methodology could also be applied to isolate larger amounts of those fatty acids or for the isolation of other minor fatty acid
Keywords: Countercurrent chromatography; Gas chromatography; Polyunsaturated fatty acid; Mass spectrometry; Podocarpus falcatus